Interlinear Translations Reduce Cognitive Load on EFL Vocabulary Acquisition - Bonilla Carvajal, Camilo Andrés (Íkala, Revista de Lenguaje y Cultura, 2025)
The use of translation in language teaching has been a source of controversial debate. Nevertheless, glossing—specifically, interlinear translations—remains an understudied learning strategy, despite having been used by learners and teachers of foreign languages since at least 1000 C. E. In the absence of a review tracing the history of interlinear translations, as well as the lack of empirical studies addressing their effect on second language reading, the present article aims to explore the role of first-language interlinear glossing by describing the results of an intervention using different reading formats in a first-semester university English reading program. In the experiment, a group of efl beginner participants (n = 48) were assigned to one of three experimental conditions, namely, reading a text in academic English (L2) with a Spanish (L1) translation using either interlinear, construed, or marginal glossing. A translation task of the same text into their first language followed immediately and was repeated past eight days. Independent anova measurements reveal an increase of translated words for the interlinear over the other two conditions, which is consistent with the hypothesis that interlinear translations allow explicit focus on word recall by reducing cognitive load in working memory, and the split-attention effect between the L2 text and its corresponding translation on a separate page. This study aims to enrich our current understanding of the impact of glossing layouts on cognitive processing.